"D-optimal experimental design" analysis in preparing optimal polyisobutylene based pressure sensitive adhesives. (October 2017) - Nasrollahzadeh, M.; Ganji, F.; Taghizadeh, S.M.; Vasheghani-Farahani, E.
Abstract: The aim of this work was to model the mechanical properties of different blends of polyisobutylene (PIB) pressure sensitive adhesives (PSAs) with different molecular weights (36, 000, 51, 000, 75, 000, 400, 000, and 1, 100, 000). The mechanical properties of PSAs are usually described by tack, peel, and shear strength which are strongly depended on the bulk viscoelastic properties of the adhesive system. It is assumed that the blends of high and low molecular weight PIB could affect these properties. According to D-optimal design of Design Expert software, various blends of five different molecular weights of PIB have been selected for study in this investigation. Using manual regression analysis, the quadratic model generated for three responses (tack, peel, and shear) was found to be statistically significant (p < 0.05). It was found that tack increases with decreasing molecular weight. It was also found that the presence of B10 and B12 as low molecular weight polymers and B50 as a high molecular weight polymer in increasing peel strength was more dominant compared with B15 and B100. Furthermore, shear strength was found to increase with an increasing concentration of the low molecular weight PIB, B15. The results have shown that statistical analysis meets theoretical expectations and they suggest desired blends of polymer for different aims.